Special pathological type of upper urinary tract malignancy—squamous cell carcinoma of the renal pelvis: A case report and literature review - Xiaodong Zhu; Zhengfei Guo; Fang Wu; An Zheng; Zhengmin Guo; Jing Li (Urology Case Reports)
Objective: To investigate the clinnical features for squamous cell carcinoma (SCC) of the renal pelvis. Methods: We analyzed the medical records of a patient diagnosed with SCC of the renal pelvis and performed a literature review. Results: SCC of the renal pelvis is a rare pathological type of upper urinary tract malignancy with nonspecific clinical features. Its diagnosis relies on postoperative pathology and immunohistochemistry. Radical resection is the gold standard for treatment. Conclusion: Patients with long-term urothelial irritation should be regularly screened, pathogenic factors should be proactively addressed, and vigilance should be maintained to prevent the development of SCC.